ROLE OF DRUG MISUSE IN PREGNANT WOMEN CAUSING CONGENITAL ANOMALIES IN CHILDREN - Dr Asna Malik; Dr Sana Bilal; Dr Zubaria Bashir; Dr Aiza Usman; Dr Hajra Mateen; Dr Ayesha Malik (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
The number of babies born with health problems has grown as a result of drug addiction by women who are fertile and drug exposure during pregnancy. Later in life, neurological and neurodevelopmental impairments may result from prenatal exposure to drugs. There are few relevant studies on the impact of psychoactive substances on the neurodevelopmental state of the fetus. It is now urgently necessary for everyone in the world to comprehend the neurodevelopmental effects of drug exposure during pregnancy. This review’s objective is to compile the most recent data and evidence about the effects of drug exposure during pregnancy on neurodevelopment. We used the phrases "drugs," "neurodevelopmental consequences," "prenatal drug exposure," and "pregnancy" to search the PubMed, Scopus, and Google Scholar databases for relevant articles. Upon reviewing the literature on drug exposure during pregnancy, it was discovered that there is evidence to suggest that fetuses and children may have some health problems. The neurodevelopmental effects of many psychoactive drugs include altered brain structure, reduced attention span, Down syndrome, ADHD, imbalances in neurotransmitter levels, autism spectrum disorder, and several structural deficiencies. More research is required to determine how exposure to psychoactive substances during pregnancy affects offspring.